The Role of the National and Political Unity Agency (Kesbangpol) in the Supervision of Islamic Community Organizations (CSOs) in Langkat Regency - Badawi, Faisal; Lubis, Maksum Syahri; Warjio, Warjio (Universitas Medan Area, 2025)
This study analyzes the role of the National and Political Unity Agency (Kesbangpol) in the supervision of Islamic Community Organizations (CSOs) in Langkat Regency and identifies supporting and inhibiting factors in its implementation. Using a qualitative descriptive approach, this research was conducted through observation, in-depth interviews, and document analysis with the main informants from Kesbangpol, representatives of Islamic organizations, and related agencies. The results of the study show that Kesbangpol carries out supervision through coordination, coaching, monitoring activities, and political counseling. Supporting factors for supervision include clear regulations, conducive social conditions, and cooperation with Islamic organizations. However, several obstacles are still faced, such as limited human resources and budgets, lack of awareness of CSOs in administrative compliance, and overlapping authority with other agencies. To overcome these obstacles, Kesbangpol needs to increase human resource capacity, strengthen coordination across agencies, and educate CSOs to be more transparent and accountable. With a more effective strategy, supervision of Islamic organizations can run more optimally in maintaining social stability and strengthening national values..